Exilic Temporality and Responsibility in Female Writers of the Spanish Republican Exile (Ogigia. Revista Electrónica de Estudios Hispánicos, 2025)
The notion of exilic time in the works of María Zambrano, María Teresa León, and Angelina Muñiz-Huberman shapes time as a disrupted experience. Exile breaks with linear chronology, merging past, present, and future. These writers portray exile not only as geographical displacement but also as a transformation of temporal perception and identity. This analysis argues that conveying knowledge about exilic time carries an ethical responsibility. Understanding this temporal experience fosters dialogue between exiles and host societies. Theorizing exile in this way becomes both an act of resistance and a commitment to memory. By exploring their own experiences, these authors seek to share insights that resonate with both exiles and those who remained in their homeland.
Keywords: Angelina Muñiz-Huberman; María Teresa León; María Zambrano; exilic time; responsibility